2014
DOI: 10.4236/jbnb.2014.53020
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Activity of Nanodiamonds in Azocoupling Reaction

Abstract: The catalytic efficiency of modified nanodiamonds (MND) in reactions of interaction between organic compounds was demonstrated on the example of azocoupling reaction (hydrogen peroxide-4-aminoantipyrine-phenol). It was found that catalytic action of MND was caused by redox active metal ions of Fe and Cu located on the MND surface. The neutralization of the ions significantly decreased catalytic properties of MND.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The process cannot be described as catalytic in the narrow sense, as DND is not (fully) recycled. However, it is noteworthy that DND do catalyze certain reactions of organic compounds, [34] e. g. reforming ethanol [35] or azo-coupling, [36] while a hybrid system of nanodiamond cores and graphene shells showed high catalytic activity and selectivity over a long period of time for dehydrogenation of ethylbenzene. [37] The catalytic properties of DND are still relatively little explored and may be very unusual.…”
Section: Resultsmentioning
confidence: 99%
“…The process cannot be described as catalytic in the narrow sense, as DND is not (fully) recycled. However, it is noteworthy that DND do catalyze certain reactions of organic compounds, [34] e. g. reforming ethanol [35] or azo-coupling, [36] while a hybrid system of nanodiamond cores and graphene shells showed high catalytic activity and selectivity over a long period of time for dehydrogenation of ethylbenzene. [37] The catalytic properties of DND are still relatively little explored and may be very unusual.…”
Section: Resultsmentioning
confidence: 99%
“…Several works have demonstrated that the presence of specific oxygen functional groups on D NPs is a prerequisite for the deposition of small MNPs , or for the covalent anchorage of organic molecules or metal complexes and the development of active catalysts. A few examples have also shown that oxygen functional groups such as carboxylates can coordinate metal ions such as Ni 2+ , Cu 2+ , or Fe 2+ , and then these can be used as catalysts for the oxidation of organic compounds in the presence of H 2 O 2 as oxidant …”
Section: Modification Of D Nps For Catalytic Applicationsmentioning
confidence: 99%
“…A few examples have also shown that oxygen functional groups such as carboxylates can coordinate metal ions such as Ni 2+ , 50 Cu 2+ , or Fe 2+ , and then these can be used as catalysts for the oxidation of organic compounds in the presence of H 2 O 2 as oxidant. 51 Analogously to other carbon materials, the introduction of oxygen-functional groups on the D NP surface can be carried out by either chemical 52 or thermal 33,47,53 methods. In a series of studies, Garcia and co-workers have shown that a homogeneous Fenton-treatment of commercial D NPs (Sigma-Aldrich, ref 636444, <10 nm) followed by hydrogen annealing at high temperature is an appropriate method for the prevalent functionalization of D NPs with hydroxyl groups (D-OH; Figure 3).…”
Section: Production Of D Npsmentioning
confidence: 99%